Sustainable Dividend Strategies: Analyzing Factors Influencing Dividend Policy in Indonesian Manufacturing Firms - Marpaung, Aldio; Brahmanto, Unggul; Muharam, Harjum (LifeSciFi, 2025)
This study aims to provide empirical evidence on the development of sustainable dividend strategies by examining the influence of profitability, liquidity, insider ownership, free cash flow, and growth opportunities on dividend policy within Indonesian manufacturing companies. The dividend policy in this research is proxied using the dividend payout ratio (DPR), reflecting the commitment of firms to distribute profits sustainably. The population for this study includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period, with purposive sampling yielding a sample of 39 companies. Secondary data, primarily financial statements sourced from the IDX's official website (www.idx.co.id), is utilized for analysis. Hypothesis testing is conducted using multiple linear regression analysis facilitated by SPSS version 26. The findings indicate that profitability, insider ownership, free cash flow, and growth opportunities significantly and positively influence sustainable dividend strategies, while liquidity does not exhibit a significant effect. This research contributes to the understanding of how manufacturing firms can align their dividend policies with sustainable practices, ultimately enhancing their competitive advantage in the market.